Efficacy of adipose stromal cells-enriched high-density fat graft combined with BTX-A for Raynaud’s phenomenon: a prospective cohort study - Chengliang Deng; Xin Liu; Miaomiao Wei; Bihua Wu; Tianhua Zhang; Shune Xiao; Peiru Min; Yixin Zhang (Arthritis Research & Therapy)
Abstract Background Conventional treatments for Raynaud’s phenomenon (RP) often show limited effectiveness due to their inability to address both vascular and inflammatory aspects. This study evaluates the combination of high-density fat grafting (HDFG) with botulinum toxin A (BTX-A) for treating RP. Methods Eleven patients with 20 affected hands diagnosed with RP were recruited and randomly assigned to receive either HDFG combined with BTX-A (intervention group, n = 11) or HDFG alone (control group, n = 9). Efficacy was assessed using Visual Analog Scale (VAS) pain scores and McCabe Cold Sensitivity Scores, along with finger ulcer healing time and infrared thermal imaging to evaluate blood perfusion improvements. Results The HDFG-BTX group showed significant improvements in hand symptoms. VAS pain scores decreased from a pre-treatment mean of 5.33 to 0.84 post-treatment (mean reduction of 4.49, p = 0.018), indicating effective pain relief. McCabe scores improved from 272.73 to 75.00 (mean reduction of 197.73, p = 0.001), demonstrating reduced cold sensitivity. Ulcer healing time was shorter in the HDFG-BTX group (14.25 days) compared to HDFG alone (25.6 days, p < 0.001), highlighting faster recovery. Infrared imaging indicated significant enhancements in blood perfusion. Conclusion HDFG combined with BTX-A is a reliable and beneficial intervention for RP, leading to high patient satisfaction.